Changes in the loading conditions induced by vagal stimulation modify the myocardial infarct size through sympathetic-parasympathetic interactions - Buchholz, Bruno (2015)
In a previous research, we described that vagal stimulation increases the infarct size by sympathetic co-activation. The aim of this study was to determine if hemodynamic changes secondary to the vagal stimulation are able to activate sympathetic compensatory neural reflexes, responsible for increasing the infarct size. A second goal was to determine if intermittent vagal stimulation avoids sympathetic activation and reduces infarct size by muscarinic activation of the Akt/glycogen synthase kinase 3 β (GSK-3β) pathway. Rabbits were subjected to 30 min of regional myocardial ischemia and 3 h of reperfusion without vagal stimulation, or the following protocols of right vagus nerve stimulation for 10 min before ischemia: (a) continuous vagal stimulation and (b) intermittent vagal stimulation (cycles of 10 s ON/50 s OFF). Continuous vagal stimulation increased the infarct size (70.7 ± 4.3 %), even after right vagal section (68.6 ± 4.1 %) compared with control group (52.0 ± 3.7 %, p < 0.05). Bilateral vagotomy, pacing, and esmolol abolished the deleterious effect, reaching an infarct size of 43.3 ± 5.1, 43.5 ± 2.1, and 46.0 ± 4.6 % (p < 0.05), respectively. Intermittent stimulation reduced the infarct size to 29.8 ± 3.0 % (p < 0.05 vs I/R). This effect was blocked with atropine (50.2 ± 3.6 %, p < 0.05). Continuous vagal stimulation induced bradycardia and increased the loading conditions and wall stretching of the atria. These changes provoked the co-activation reflex of the sympathetic nervous system, observed by the rise in plasmatic catecholamine levels, which increased the infarct size. Sympathetic co-activation was abolished by continuous vagal stimulation with constant heart rate or parasympathetic deafferentation. Intermittent vagal stimulation attenuated the sympathetic tone and reduced the infarct size by the muscarinic activation of the Akt pathway and GSK-3β inhibition. Continuous stimulation only phosphorylated Akt and GSK-3β when esmolol was administered.